Economic aspects of Serbian comparative advantages in exports of vegetable matter - Ignjatijević, Svetlana; Milojević, Ivan; Božić, Dijana (Economics of Agriculture, 2018)
Increase of exports of goods and services is needed in domestic economy in order to reduce foreign trade deficit. Reduction of the negative balance directly affects the level of funds needed to pay for imports and service external debt The paper points out the tendency of foreign trade and macroeconomic aspects of exports. The paper seeks to quantify the degree of comparative advantage of Serbia's exports of medicinal, aromatic and spice herbs and other raw plant materials.